2014
DOI: 10.1159/000366265
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Novel Oral Anticoagulants in Patients with Cervical Artery Dissections

Abstract: Background: American and European guidelines support antiplatelet agents and anticoagulants as reasonable treatments of cervical artery dissection (CAD), though randomized clinical trials are lacking. The utility of novel oral anticoagulants (NOAC), effective in reducing embolic stroke risk in non-valvular atrial fibrillation (NVAF), has not been reported in patients with CAD. We report on the use, safety, and efficacy of NOACs in the treatment of CAD. Methods: We retrospectively identified patients diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 31 publications
0
38
0
Order By: Relevance
“…Despite that, anticoagulation therapy is still often used in practice as a stroke prevention strategy in patients with cervical artery dissection. 43 Anticoagulation has been historically used in stroke prevention without good scientific evidence, which triggered several randomized trials including Warfarin-Aspirin Symptomatic Intracranial Disease (WASID) and Warfarin-Aspirin Recurrent Stroke Study (WARSS) that showed no benefit of Warfarin over Aspirin in reducing stroke recurrence 44-47 . The same argument likely holds for cervical arterial dissection where anticoagulation has been historically used in secondary stroke prevention despite the lack of evidence of superiority over aspirin.…”
Section: Resultsmentioning
confidence: 99%
“…Despite that, anticoagulation therapy is still often used in practice as a stroke prevention strategy in patients with cervical artery dissection. 43 Anticoagulation has been historically used in stroke prevention without good scientific evidence, which triggered several randomized trials including Warfarin-Aspirin Symptomatic Intracranial Disease (WASID) and Warfarin-Aspirin Recurrent Stroke Study (WARSS) that showed no benefit of Warfarin over Aspirin in reducing stroke recurrence 44-47 . The same argument likely holds for cervical arterial dissection where anticoagulation has been historically used in secondary stroke prevention despite the lack of evidence of superiority over aspirin.…”
Section: Resultsmentioning
confidence: 99%
“…Catheter angiography has been the gold standard for the diagnosis of arterial dissections. [21][22][23][24] The most common finding on angiography is the one called "string sign", a long segment of narrowed lumen. The pathognomonic features of dissection, such as an intimal flap or a double lumen, are found in less than 10% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Antiplatelet treatments included aspirin, dipyridamole, or clopidogrel alone or in combination. 14,[19][20][21][22] For patients assigned to anticoagulation, treatment with heparin (either unfractionated heparin or a therapeutic dose of low-molecular weight heparin) was followed by warfarin, aiming for an international normalized ratio of 2-3. Novel oral anticoagulants were not used.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, trials are underway to assess NOACs in secondary prevention after cryptogenic stroke. They may be used for stroke prevention in cervical artery dissection and cerebral venous sinus thrombosis [16] . If NOACs prove to be effective for these entities as well, the prevalence of anticoagulation may rise even further.…”
Section: Discussionmentioning
confidence: 99%